Specificity of Emotion Regulation Processes in Depression: A Network Analysis - Depoorter, Jente; De Raedt, Rudi; Berking, Matthias; Hoorelbeke, Kristof (Cognitive Therapy and Research, 2024)
Background: Maladaptive emotion regulation has received a lot of attention as a potential mechanism underlying major depressive disorder (MDD). However, less is known about the role of adaptive emotion regulation skills and its specificity for MDD. The Adaptive Coping with Emotions model provides a framework for this, distinguishing early (Awareness, Sensations, Clarity, Understanding) and later processes (Modification, Acceptance, Tolerance, Readiness to confront and Effective Self-Support) relevant for emotion regulation. Methods: The current study (N = 291) applied Network Analysis with Fused Graphical Lasso to jointly estimate emotion regulation networks in MDD (N = 160) and a control sample (N = 131). Within the two obtained network models, we investigated how different aspects of emotion regulation cluster together. In addition, level of centrality and unique associations between constructs were modeled. Permutation tests were applied to identify significant differences between both networks. Results: Two communities were detected, with one including variables related to preparatory processes in emotion regulation and the other including variables related to regulation processes. Additionally, ‘Identifying and Labeling’ was ranked among the most central nodes. Furthermore, our results suggest similar pathways connecting emotion regulation skills in MDD and controls. Conclusions: The results highlight the existence of different processes in emotion regulation and provide further evidence for emotion regulation as a transdiagnostic concept.
CRIS-Team Scopus Importer:2024-09-13
Keywords: Depression; Emotion regulation; Emotion regulation skills; MDD; Network analysis